MOTIVASI CALON KEPALA DESA DALAM PEMILIHAN KEPALA DESA DI DESA SIMALINYANG KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR TAHUN 2017 - Rezki, Zubriati; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
With the enactment of Law Number 6 of 2014 concerning Villages, it is a great opportunity for every village throughout Indonesia to be able to develop their potential independently in accordance with the needs of each village in realizing the welfare of their community. The existence of the Village Head is very important in developing the village's potential to improve village developmentThis study aims to: 1) know and understand the motivations of prospective Village Heads to win the Position of the Village Chief. 2) knowing and understanding the steps taken by the Village Chief Candidates to win the Position of the Village Chief. This study uses a qualitative approach with a type of descriptive research. Data collection techniques used in this study were interview observation and documentation.Research results from the motivational variables of the researchers used an approach from Maslow's Theory consisting of 5 Needs. While the steps taken by prospective researchers carried out 2 approaches, namely an approach to the community and youth and an approach through close relatives. From the results of the study, the motivation of the four prospective village heads was tiered. Namely physical needs, safety and security needs, social needs, the need for appreciation or prestige, actualization needs.Keywords: Motivation, Steps for Candidates for Village Heads, PILKADES